1991
DOI: 10.1016/0304-3940(91)90756-j
|View full text |Cite
|
Sign up to set email alerts
|

Protease nexin-1 activity in cultured Schwann cells

Abstract: We report that protease nexin-1 (PN-1), a serine protease inhibitor known to have neurite-promoting effects, is made by Schwann cells in tissue culture. Three modalities have been used to demonstrate the presence of PN-1 in Schwann cell cultures. Immunostaining of the cultures with anti-PN-1 antibody gives positive staining over cells and matrix. Western blots of Schwann cell conditioned medium (CM) using anti-PN-1 antibody show a band that co-migrates with the PN-1 standard at 45 kDa. Biochemical assay for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Several proteins were previously shown to increase neurite growth [e.g., SPARC (24)(25)(26), meteorin (27,28), pleiotrophin (29), and glial cell line-derived neurotrophic factor family receptor a-1 (30)]. Other proteins are directly involved in regeneration [e.g., protease nexin-1 (glia-derived nexin) (31)(32)(33)(34)(35), galectin-1 (36), and ADAM proteins (37,38)]. Moreover, axon guidance cues were identified such as neural cell adhesion molecule 1, neuropilin1/2 and semaphorin 3A (39,40), secreted frizzled-related protein 1 (41), and furin (42).…”
Section: Composition Of Schwann Cell Secretomesmentioning
confidence: 99%
“…Several proteins were previously shown to increase neurite growth [e.g., SPARC (24)(25)(26), meteorin (27,28), pleiotrophin (29), and glial cell line-derived neurotrophic factor family receptor a-1 (30)]. Other proteins are directly involved in regeneration [e.g., protease nexin-1 (glia-derived nexin) (31)(32)(33)(34)(35), galectin-1 (36), and ADAM proteins (37,38)]. Moreover, axon guidance cues were identified such as neural cell adhesion molecule 1, neuropilin1/2 and semaphorin 3A (39,40), secreted frizzled-related protein 1 (41), and furin (42).…”
Section: Composition Of Schwann Cell Secretomesmentioning
confidence: 99%
“…Since previous studies showed that neurons contacting astrocytes are relatively resistant to Ca*+-mediated toxicity (Mattson and Rychlik, 1990) and because PN-1 is produced by astrocytes (Rosenblatt et al, 1987;Reinhard et al, 1988;Milligan et al, 1991;Reinhard et al, 1994), we examined Ca2+ responses to thrombin in neurons alone compared to neurons contacting astrocytes. To begin, we found rest levels of [Ca*+], to be 1.5-fold higher in neurons not contacting astrocytes as compared with neurons contacting astrocytes.…”
Section: Pn-1 Attenuates the Elevation Of [Ca2+] That Mediates Glucomentioning
confidence: 99%
“…The high molecular weight PNI immunoreactivity found in both control and injured nerves has not been previously noted (Meier et al, 1989). It is not clear whether this PNI band represents a complex with an unidentified target protease, other than thrombin, or is a dimer, as is sometimes seen with purified PNI preparations (Mulligan et al, 1991). It is reasonable to suggest that endogenous thrombin/PNI complexes, if preformed, might be cleared quickly by a receptor similar or identical to the a2-macroglobulin/low density lipoprotein receptor-related protein (Orth et al, 1992;Bu et al, 1994), limiting our ability to detect them.…”
Section: Discussionmentioning
confidence: 78%